Van der Waals Superstructure and Twisting in Self-Intercalated Magnet with Near Room-Temperature Perpendicular Ferromagnetism - Coughlin, Amanda L; Xie, Dongyue; Zhan, Xun; Yao, Yue; Deng, Liangzi; Hewa-Walpitage, Heshan; Bontke, Trevor; Chu, Ching-Wu; Li, Yan; Wang, Jian; Fertig, Herbert A; Zhang, Shixiong (Nano letters, 2021)
The emergence of van der Waals (vdW) magnets has created unprecedented opportunities to manipulate magnetism for advanced spintronics based upon all-vdW heterostructures. Among various vdW magnets, Cr1+δTe2 possesses high temperature ferromagnetism along with possible topological spin textures. As this system can support self-intercalation in the vdW gap, it is crucial to precisely pinpoint the exact intercalation to understand the intrinsic magnetism of the system. Here, we developed an iterative method to determine the self-intercalated structures and show evidence of vdW “superstructures” in individual Cr1+δTe2 nanoplates exhibiting magnetic behaviors distinct from bulk chromium tellurides. Among 26,332 possible configurations, we unambiguously identified the Cr-intercalated structure as 3-fold symmetry broken Cr1.5Te2 segmented by vdW gaps. Moreover, a twisted Cr-intercalated layered structure is observed. The spontaneous formation of twisted vdW “superstructures” not only provides insight into the diverse magnetic properties of intercalated vdW magnets but may also add complementary building blocks to vdW-based spintronics.